Flag of Convenience Practice: A Threat to Maritime Safety and Security - Bakar Hamad, Hamad (IJRDO - Journal of Social Science and Humanities Research, 2016)
The skyrocketing number of flag of convenience practices in recent years has been partly due to the existence of loopholes in maritime jurisdictions which are in favour of flag of conveniences and unethical ship owners. Through these loopholes, under flag of conveniences, owners can purposely sail substandard and ungoverned ships, predominantly on the high seas, where an individual state’s jurisdictions cannot reach. Consequently, the ship owners take advantage of the inability of the flag of convenience to govern its own ships, which compromises important maritime safety and security norms. This study investigates maritime safety and security threats posed by escalation of flag of convenience practices. The most serious violations of maritime norms take place in areas relating to marine pollution, abuse of seafarers, concealments of the true identity of ship owners, illegal fishing, drags, human trafficking and maritime terrorism. The study concludes that flagging out for economic reasons is not a problem. Nevertheless, purposely flagging out to the less-regulated flags is what concerns the international maritime community.